Roles of glycosylation on the antifungal activity and apoplast accumulation of StAPs (Solanum tuberosum aspartic proteases) - Pagano, Mariana (2007)
Specific roles of glycosylation appear to be protein-dependent. Plant aspartic proteases (APs) contain two or more consensus N-glycosylation sites; however, the importance of them is not well understood. StAPs (Solanum tuberosum aspartic proteases) are bifunctional proteins with both proteolytic and antimicrobial activities. These proteins are accumulated into the intercellular washing fluid of potato tubers and leaves after wounding or infection. In this paper we investigated the importance of glycosylation on the StAPs apoplast accumulation, biochemical parameters, and fungicidal activity. Assays to evaluate the importance of StAPs glycosylation groups by using glycosylation inhibitors demonstrate that carbohydrate portions are essential to StAPs accumulation into the apoplast of tubers and leaves after wounding or detachment, respectively. Bifunctional activity of StAPs is differentially affected by this post-translational modification. Results obtained show that not significant changes were produced in the physicochemical properties after StAPs deglycosylation (pH and thermal-optimum activity and index of protein surface hydrophobicity). Otherwise, StAPs antifungal activity is affected by deglycosylation. Deglycosylated StAPs (dgStAPs) fungicidal activity is lower than native StAPs at all concentrations and times assayed. In summary, glycosylation has not a significant role on the StAPs conformational structure. However, it is involved in the StAPs subcellular accumulation and antifungal activity suggesting that it could be necessary for StAPs membrane and/or protein interactions and subsequently its biological function(s).